The effects of silica-coated Y2O2S:Eu3+ red phosphor on the lighting properties of the light-emitting diode - Phuc Dang Huu; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
The red phosphor Y2O2S:Eu3+ coated with silica (SiO2) nanocomposite was synthesized using the sol-gel method with dip-coating technique. The purpose of coating the poly (methyl methacrylate) (PMMA)-SiO2 composite on Y2O2S:Eu3+ phosphor’s surface is to protect the phosphor and improve its scattering ability. The three primary ingredients of coating composition include methyl methacrylate (MMA) monomer, tetraethyl orthosilicate (TEOS), and SiO2 nanoparticles. Via Mie scattering theory, the scattering of SiO2 is examined, which primarily determines the scattering of PMMA-SiO2-coated Y2O2S:Eu3+. The larger particles of SiO2 in the coating composite leads to better scattering properties. When being applied in the dual-film remote phosphor configuration of a LED, SiO2@Y2O2S:Eu3+ considerably enhances the CRI and the color quality scale (CQS). The highest CRI and CQS can be observed at approximately 85 and 74 with 23 %wt. and 26 %wt. the concentration of SiO2@Y2O2S:Eu3+, respectively. Neverthless, the illuminating beam of the package gradually declines as the concentration of SiO2@Y2O2S:Eu3+ go up, which might be ascribed to excessive scattering occurrences in the double-layer remote package.